WHO human health risk assessment toolkit : chemical hazards (World Health Organization, 2010)
The purpose of the WHO Human Health Risk Assessment Toolkit: Chemical Hazards is to provide its users with guidance to identify, acquire and use the information needed to assess chemical hazards, exposures and the corresponding health risks in their given health risk assessment contexts at local and/or national levels. The Toolkit provides road maps for conducting a human health risk assessment, identifies information that must be gathered to complete an assessment and provides electronic links to international resources from which the user can obtain information and methods essential for conducting the human health risk assessment.By doing so, the Toolkit also raises awareness and promotes the use of globally accepted risk assessment information that has been developed by international organizations such as WHO, the Food and Agriculture Organization of the United Nations, the United Nations Environment Programme, the Codex Alimentarius Commission and OECD for use in countries. The Toolkit has been developed for public health and environmental professionals, regulators, industrial managers and other decision-makers with at least some training in the principles of risk assessment who are responsible for conducting human health risk assessments and making decisions on whether to take action to manage human health risks associated with exposure to chemicals.
IPCS harmonization project document ; no. 8.
Keywords: Environmental Exposure; hygiena; toxikologie; hodnocení rizik; nebezpečné látky; Hazardous Substances; Risk Assessment; vystavení vlivu životního prostředí